2007
DOI: 10.1002/met.44
|View full text |Cite
|
Sign up to set email alerts
|

The economic value of weather forecasts for decision‐making problems in the profit/loss situation

Abstract: This article presents a method to estimate the economic value of forecasts for profit-oriented enterprise decision-making problems related to the levels of preparations for goods or services. The sales of goods or services in the study are supposed to be influenced and predicted by meteorological variables. Value is calculated in terms of monetary profit (or benefit) returned from the user's decision under the specific payoff structure, which is represented by a profit/loss ratio model. The decision is determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Consequently, it is necessary to normalize the difference by the relative increase in expected satisfaction level to that of a perfect forecast. The concept of a normalized scale was established as a value score in previous studies (Wilks, ; Mylne, ; Lee and Lee, ). The relative increased satisfaction level, i.e., value score (VS) of forecasts can be defined as shown by Equation .…”
Section: Satisfaction Value Scores Of Individuals and Groups Using Prmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, it is necessary to normalize the difference by the relative increase in expected satisfaction level to that of a perfect forecast. The concept of a normalized scale was established as a value score in previous studies (Wilks, ; Mylne, ; Lee and Lee, ). The relative increased satisfaction level, i.e., value score (VS) of forecasts can be defined as shown by Equation .…”
Section: Satisfaction Value Scores Of Individuals and Groups Using Prmentioning
confidence: 99%
“…The technical understanding of probabilistic precipitation forecasts is not an essential factor in the use of forecasts (Morss et al , ). Nevertheless, many researchers have strived to improve decision‐makers' confidence in weather forecasts through value evaluation of probabilistic forecast (Thompson and Brier, ; Murphy, ; Epstein and Murphy, ; Wilks, ; Mylne, ; Lee and Lee, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially evident for precipitation forecasts as some users need quantitative precipitation data [5] while others are interested in the rainfall threshold and spatial scale [6]. Special procedures should be used to provide profit-oriented enterprises with the necessary information to make proper decisions [7,8]. On the other hand, economic benefits from improved forecast accuracy should be estimated to justify the investments into the weather service [9].…”
Section: Introductionmentioning
confidence: 97%
“…It is well-known that forecasting whether a rainfall event of concern will occur in a deterministic or probabilistic way is quite useful for the enterprise, government, and agricultural decision-makers (Katz and Murphy, 1997;Lee and Lee, 2007). As for the traditional Probabilistic Quantitative Precipitation Forecast (PQPF), many works (e.g., Eckel and Walters, 1998;Buizza et al, 1999;Hamill et al, 2008) have shown its limitation for 6-15 day precipitation events since the corresponding skill generally decreases significantly after 6 days; this is because it lacks the sharpness to discriminate which events occurred and which events did not in this period.…”
Section: Introductionmentioning
confidence: 99%